Telemedicine Versus Clinic Visit: A pilot study of patient satisfaction and recall of diet and exercise recommendations from survivorship care plans. - Sprague, Sharon Likely; Holschuh, Carrie (Clinical Journal of Oncology Nursing, 2019)
BACKGROUND: Telemedicine is a growing approach to providing health care but a relatively new model for cancer survivorship services. OBJECTIVES: This quantitative, quasiexperimental pilot research study compared patient satisfaction and recall of nutrition and exercise recommendations for in-person clinic visits versus telemedicine appointments. METHODS: Participants were stage 0–III cancer survivors who received their survivorship care plans from a nurse practitioner (NP). Following their clinic or telephone appointment, patients were sent a link to a survey that included demographic, patient satisfaction, and recall of diet and exercise recommendation questions. Fifty-two survivors completed the survey, of whom 38 had a clinic appointment and 14 had a telephone appointment. FINDINGS: There was no statistically significant difference between the mean patient satisfaction or recall of healthy weight, exercise, and nutrition recommendations between cancer survivors receiving their survivorship care plan by telephone versus a clinic appointment with an NP.